Short-term expansion planning of radial electrical distribution systems using mixed-integer linear programming - Goncalves, Rogerio R.; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP] (Inst Engineering Technology-iet, 2015)
This study presents a mixed-integer linear programming (MILP) model to solve the short-term expansion planning problem of radial electrical distribution systems. The proposed model defines the construction of new circuits, the reconductoring of existing circuits, the allocation of capacitor banks (as well as the type and the number of units in operation) and the allocation of voltage regulators to minimise the total annualised investment and operation costs. In the proposed formulation, the steady-state operation of the radial distribution system is mathematically modelled through linear expressions. The use of an MILP model guarantees convergence to optimality by using existing classical optimisation tools. The model was implemented in the mathematical modelling language AMPL and solved using the commercial solver CPLEX. A 54-node test system and 201-node real distribution system were used to demonstrate the accuracy of the mathematical model, as well as the efficiency of the proposed solution technique.
Keywords: Linear programming; Integer programming; Power capacitors; Voltage regulators; Radial electrical distribution systems; Mixed-integer linear programming